Structures and functions of invertebrate glycosylation - Feifei Zhu; Dong Li; Keping Chen (Open Biology, 2019)
Glycosylation refers to the covalent attachment of sugar residues to a protein or lipid, and the biological importance of this modification has been widely recognized. While glycosylation in mammals is being extensively investigated, lower level animals such as invertebrates have not been adequately interrogated for their glycosylation. The rich diversity of invertebrate species, the increased database of sequenced invertebrate genomes and the time and cost efficiency of raising and experimenting on these species have enabled a handful of the species to become excellent model organisms, which have been successfully used as tools for probing various biologically interesting problems. Investigation on invertebrate glycosylation, especially on model organisms, not only expands the structural and functional knowledgebase, but also can facilitate deeper understanding on the biological functions of glycosylation in higher organisms. Here, we reviewed the research advances in invertebrate glycosylation, including N- and O-glycosylation, glycosphingolipids and glycosaminoglycans. The aspects of glycan biosynthesis, structures and functions are discussed, with a focus on the model organisms Drosophila and Caenorhabditis. Analytical strategies for the glycans and glycoconjugates are also summarized.